Novel Approach to Multi Constraints Reactive Multicast Routing Protocol for MANET - Madhu Babu, D; Ussenaiah, M (International Journal of Computer Sciences and Engineering, 2019)
Mobile Ad Hoc Network (MANET) is a widespread research area, where the protocols face challenges due to its dynamic network topology. The adaptive network is an emerging technology that draws attraction as it is cheaper, concise and powerful. In applications where sharing of information is essential, MANET uses multicast routing protocols, as it is easily deployable. The paper describes various system models (like energy model, LLT model, mobility model etc.) related to MANET. The objective of this paper is to introduce multicast routing in MANET with the aid of tree-based clustering and optimization by proposing Cuckoo Search (CS) and M-Tree based Multicast Ad hoc On-demand Distance Vector (CS-MAODV).